2015
DOI: 10.1002/cam4.476
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of sorafenib treatment and hepatic arterial infusion chemotherapy for advanced hepatocellular carcinoma: a comparative study using the propensity score matching method

Abstract: While sorafenib (SFN) is the established worldwide standard therapeutic agent for advanced hepatocellular carcinoma (HCC), hepatic arterial infusion chemotherapy (HAIC) is also considered a favorable treatment for some advanced HCCs. This study aimed to evaluate each treatment and provide an optimal therapeutic choice for advanced HCCs. We analyzed 72 patients treated with SFN and 128 patients receiving HAIC. Both treatment groups were analyzed for prognostic and disease progression factors, and matched pair a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“… 8 , 12 14 However, some other studies had reported conflicting results. 10 , 11 , 15 Meta-analysis is a method that combines data from all eligible studies, and has the advantages of reducing random error, obtaining more precise estimates, and defining the effect of clinical interventions more precisely. 18 , 19 Hence, meta-analysis is an eligible method to resolve such conflicts.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 12 14 However, some other studies had reported conflicting results. 10 , 11 , 15 Meta-analysis is a method that combines data from all eligible studies, and has the advantages of reducing random error, obtaining more precise estimates, and defining the effect of clinical interventions more precisely. 18 , 19 Hence, meta-analysis is an eligible method to resolve such conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective cohort study, while there was no significant difference in survival between the sorafenib group and the HAIC group, survival was significantly better in the HAIC group than in the sorafenib group among patients with macroscopic vascular invasion (14 mo vs 7 mo, P = 0.005)[ 72 ]. A propensity score matched analysis also showed no significant differences in survival or disease progression between the two groups, while PFS was significantly longer in the HAIC group than in the sorafenib group, particularly for patients with portal vein invasion and/or without extrahepatic spread[ 73 ]. On the other hand, survival was favorable in patients with HCC refractory to TACE treated with sorafenib rather than HAIC[ 74 ].…”
Section: Sorafenib Vs Haicmentioning
confidence: 99%
“…HAIC was implemented using two regimens: 102 patients were treated by the low-dose cisplatin + 5-fluorouracil regimen, and 26 were treated by the subcutaneous IFN-α + 5-fluorouracil regimen of HAIC. Analysis of 53 patients selected from each of the sorafenib and HAIC groups based on the propensity score-matching method showed no significant differences in survival ( p = 0.750) [27]. Shiozawa et al [28] compared sorafenib versus HAIC with cisplatin and 5-fluorouracil for in 80 patients with advanced HCC.…”
Section: Alternative Treatment Strategiesmentioning
confidence: 99%
“…In addition, two studies compared HAIC and sorafenib in patients with advanced HCC using propensity score matching. Fukubayashi et al [27] analyzed 72 patients treated with sorafenib and 128 patients receiving HAIC. In this study, more than 50% of the patients had vascular invasion.…”
Section: Alternative Treatment Strategiesmentioning
confidence: 99%